Distributed Computing in Sensor Systems - Nikoletseas, S. (Springer, 2017)
The book constitutes the refereed proceedings of the 4th International Conference on Distributed Computing in Sensor Systems, DCOSS 2008, held on Santorini Island, Greece, in June 2008.